Revision of the genus Euarestoides Benjamin (Diptera: Tephritidae) - Savaris, Marcoandre; Norrbom, Allen L.; Marinoni, Luciane; Lampert, Silvana (Zootaxa, 2019)
Species of the genus Euarestoides Benjamin (Diptera: Tephritidae) are revised. Euarestoides comprises six species: E. abstersus (Loew) (Bahamas, eastern Canada and USA); E. acutangulus (Thomson) (Canada, Chile, Colombia, Cuba, Dominican Republic, Ecuador, Mexico, Peru, Puerto Rico, Trinidad & Tobago, USA, and Venezuela); E. bimaculatus Savaris & Norrbom, n. sp. (Peru); E. dreisbachi Foote (Guatemala, Mexico, Peru); E. pereirai Savaris & Norrbom, n. sp. (Brazil); and E. rionegrensis Savaris & Norrbom, n. sp. (Colombia). A key to the known species of the genus is provided, as well as descriptions, illustrations, distributions, notes on the biology and host plant data for each species.